2017
DOI: 10.18632/oncotarget.15960
|View full text |Cite
|
Sign up to set email alerts
|

Suppressive role exerted by microRNA-29b-1-5p in triple negative breast cancer through SPIN1 regulation

Abstract: MiR-29 family dysregulation occurs in various cancers including breast cancers. We investigated miR-29b-1 functional role in human triple negative breast cancer (TNBC) the most aggressive breast cancer subtype. We found that miR-29b-1-5p was downregulated in human TNBC tissues and cell lines. To assess whether miR-29b-1-5p correlated with TNBC regenerative potential, we evaluated cancer stem cell enrichment in our TNBC cell lines, and found that only MDA-MB-231 and BT-20 produced primary, secondary and tertiar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
108
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(109 citation statements)
references
References 57 publications
0
108
0
Order By: Relevance
“…Here, we show that early during infection, HP0175 is associated with augmented expression of miR29b-1-5p. Other independent studies have shown miR-29b-1-5p expression in human triple negative breast cancer cells (Ferrante et al, 2017). miR-29b-1-5p expression is repressed in an hp0175 knockout strain compared with the wild type, and recombinant HP0175 induces miR-29b-1-5p expression.…”
Section: Role Of Hp0175 In Mir-29b-1-5p/phlpp1dependent Mmp Inductimentioning
confidence: 77%
See 1 more Smart Citation
“…Here, we show that early during infection, HP0175 is associated with augmented expression of miR29b-1-5p. Other independent studies have shown miR-29b-1-5p expression in human triple negative breast cancer cells (Ferrante et al, 2017). miR-29b-1-5p expression is repressed in an hp0175 knockout strain compared with the wild type, and recombinant HP0175 induces miR-29b-1-5p expression.…”
Section: Role Of Hp0175 In Mir-29b-1-5p/phlpp1dependent Mmp Inductimentioning
confidence: 77%
“…It is associated with a higher grade of gastric inflammation (Oghalaie et al, 2016). Other independent studies have shown miR-29b-1-5p expression in human triple negative breast cancer cells (Ferrante et al, 2017). Our earlier studies have shown that depending on the time and/or the dose of infection, HP0175 modulates host cell signalling to trigger either autophagy (Halder et al, 2015) or apoptosis (Basak et al, 2005) in gastric epithelial cells.…”
Section: Role Of Hp0175 In Mir-29b-1-5p/phlpp1dependent Mmp Inductimentioning
confidence: 95%
“…The structure of SPIN1 has been solved by X-ray crystallography [31][32][33] . As a result, multiple researchers are pursuing the development of a SPIN1 inhibitor 10,16,[40][41][42][43] . C11orf84, which was recently renamed SPINDOC by Bae and colleagues 9 , is a SPIN1-interacting protein that is less well understood, and the complex containing these two proteins remains poorly characterized.…”
Section: Discussionmentioning
confidence: 99%
“…We demonstrate the striking capabilities of this technology using a pair of proteins, Spindlin1 (SPIN1) and SPINDOC (c11orf84), which have previously been proposed to directly interact in biochemical 9 and computational 3 studies. SPIN1 is a well characterized histone methylation reader [9][10][11][12][13][14][15][16][17][18][19][20][21] , while SPINDOC has only been defined by its ability to bind SPIN1 9 . In this study, we first characterize the direct interaction and co-diffusion of SPIN1 and SPINDOC in live cells using imaging methods.…”
Section: Introductionmentioning
confidence: 99%
“…Of these, the expression of miR-29b-1-5p was significantly upregulated, consistent with our Brca1 Table 3). Interestingly, SPIN1 is among the predicted targets and have been previously identified to be directly targeted by miR-29b-1-5p in breast cancer cell lines 19 .…”
Section: Brca1 Binds To Mirna Promoters and Regulates Mir-29b-1-5p Lementioning
confidence: 99%